Structural and morphological changes in Poly(caprolactone)/poly(vinyl chloride) blends caused by UV irradiation - Martins-Franchetti, Sandra Mara [UNESP]; Campos, Adriana [UNESP]; Egerton, Terry A.; White, Jim R. (Springer, 2008)
Films made from a blend of poly(epsilon-caprolactone) and poly(vinyl chloride) (PCL/PVC) retained high crystallinity in a segregated PCL phase. Structural and morphological changes produced when the films were exposed to high potency ultraviolet (UV) irradiation for 10 h were measured by UV-Vis spectroscopy (UV-Vis), Fourier Transform Infrared Spectroscopy (FTIR), and Scanning Electron Microscopy (SEM). They were different to those observed with homopolymer PCL and PVC films treated under the same conditions. The FTIR spectra of the PCL/PVC blend suggest that blending decreased the susceptibility of the PCL to crystallize when irradiated. Similarly, although scanning electron micrographs of PCL showed evidence of growth of crystalline domains, particularly after UV irradiation, the images of PCL/PVC were fairly featureless. It is apparent that the degradation behavior is strongly influenced by the interaction of the two polymers in the amorphous phase.